Funk & Wagnalls standard dictionary of folklore, mythology and legend Fried, associate editor. - Leach, Maria (Funk & Wagnalls, 1949)
Contains over 4000 entries about folk stories and songs, gods, heroes, fairies and demons, angels and devils, ogres,guardian spirits, witches, vampires and zombies of many cultures